1983
DOI: 10.1901/jaba.1983.16-111
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Echolalia on Acquisition and Generalization of Receptive Labeling in Autistic Children

Abstract: This investigation, consisting of two experiments, was designed to assess the effects of autistic immediate echolalia on acquisition and generalization of receptive labeling tasks. Experiment 1 addressed whether autistic children could use their echolalia to facilitate acquisition. The results indicated that incorporating echolalia (echo of the requested object's label) into the task before manual response (handing the requested object to the experimenter) facilitated receptive labeling. Experiment 2 was desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
3
2

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 34 publications
4
54
3
2
Order By: Relevance
“…Thus, although patterns of non-verbal stereotypies appeared consistent with the interference theory, these data suggest that verbal stereotypy may instead have a facilitative effect on learning. This effect has also been demonstrated in echolalic children with autism (Charlop, 1983) and across treatment (Epstein, Taubman, & Lovaas, 1985).…”
Section: Stereotypy and Learningmentioning
confidence: 57%
“…Thus, although patterns of non-verbal stereotypies appeared consistent with the interference theory, these data suggest that verbal stereotypy may instead have a facilitative effect on learning. This effect has also been demonstrated in echolalic children with autism (Charlop, 1983) and across treatment (Epstein, Taubman, & Lovaas, 1985).…”
Section: Stereotypy and Learningmentioning
confidence: 57%
“…A possible practical implication of the present data is that, although the inclusion of collateral echoic response requirements in listener training may facilitate acquisition (Charlop 1983;Koegel et al 1981;Leung and Wu 1997) or facilitate the emergence of vocal responding (Ezell and Goldstein 1989;Hawkins et al 2009) for children with language delays due to developmental disabilities, they may not do so for typically developing children who already have extensive verbal repertoires. Instead, other types of interventions might be considered for this population if listener training fails to produce highly accurate vocal tacts and intraverbals.…”
Section: Discussionmentioning
confidence: 89%
“…In this context, it may be noted that several studies conducted with children with developmental disabilities have found an effect of echoic response requirements during listener training on the acquisition of the listener repertoire, without measuring effects on derived vocal responding (Charlop 1983;Koegel et al 1981;Leung and Wu 1997). A possible reason for this enhanced effect on acquisition is that the echoic response requirement may serve as a differential observing response (e.g., Dube and McIlvane 1999) to the dictated sample stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…For each item, postintervention means were higher than preintervention means. These data were also analyzed using a sign test for each item across subjects and raters (Siegel, 1956 (Rimland, 1964 Thus, the tendency to echo may have been advantageous (e.g., Charlop, 1983;Prizant, 1983) with the video modeling procedure.…”
Section: Social Validationmentioning
confidence: 99%